2014
DOI: 10.3390/pharmacy2010050
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Simulation: A Scottish, Student-Led Perspective with Lessons for the UK and Beyond

Abstract: Compared to the nursing and medical professions, simulation-based pharmacy education is a relatively new mode of supporting learning, although one that is growing rapidly to meet the training needs of a new generation of healthcare professionals. Within the UK (and particularly Scotland), access to the clinical environment through the more traditional route of placement is limited, and simulation offers a partial solution to this problem. As is well-established, simulation-if used appropriately-also offers exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…International literature continues to reinforce the need for and the positive effects associated with the use of simulation-based methodologies as part of pharmacy educational programs (Kirwin et al 2013;Loke et al 2011;Murdoch et al 2014;Regan et al 2014;Ruehter et al 2012;Salter et al 2014;Smith and Benedict 2015;Veettil and Rajiah 2016;Vyas et al 2013). However, there is limited information on Australian studies that involved the development, implementation, and evaluation of hospital-based simulation training packages within tertiary education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…International literature continues to reinforce the need for and the positive effects associated with the use of simulation-based methodologies as part of pharmacy educational programs (Kirwin et al 2013;Loke et al 2011;Murdoch et al 2014;Regan et al 2014;Ruehter et al 2012;Salter et al 2014;Smith and Benedict 2015;Veettil and Rajiah 2016;Vyas et al 2013). However, there is limited information on Australian studies that involved the development, implementation, and evaluation of hospital-based simulation training packages within tertiary education.…”
Section: Discussionmentioning
confidence: 99%
“…International literature emphasizes the need to utilize an assortment of technology-based learning environments to train and educate health professionals (Cook et al 2011;Keppell et al 2015) and specifically for pharmacists (Fejzic and Barker 2015;Smith and Benedict 2015). Multiple studies support embedding technology-enhanced, simulation-based education into pharmacy curricula, such as online learning that is enriched by pre-recorded role plays with actors or simulated participants, virtual patients, task simulations and/or interactive platforms that simulate a specific skill or competency (Fejzic and Barker 2015;Kirwin et al 2013;Loke et al 2011;Regan et al 2014;Salter et al 2014;Smith and Benedict 2015;Veettil and Rajiah 2016;Vyas et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Reflections on this aspect of the work have been published as part of another study (Regan et al, 2014), but essentially it was suggested that unrealistic environments deprive the student of the opportunity to experience the reality of practice, meaning s/he is not well prepared for the workplace.…”
Section: Addressing the Mismatch Between 'Ideal' And 'Real' Clinical mentioning
confidence: 99%
“…The benefits of simulation are many, not least the fact that such activities can support students in skills acquisition without exposing patients to risk and therefore potentially improving safety. The level of control that can be exerted over the simulation environment is higher compared with ‘real’ clinical situations 9 - 11 .…”
Section: Introductionmentioning
confidence: 99%